2018
DOI: 10.21577/0103-5053.20180001
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Biodistribution in Rats after Chronic Exposure to Mercury Chloride

Abstract: This study aimed to evaluate the distribution of mercury in rats after controlled chronic exposure to three different doses of HgCl 2 for 30 days. Samples of blood, brain, liver, testis, heart, and kidneys were collected for mercury determination. Although the rats were exposed to different doses, the Hg levels in blood were similar among the groups under study. However, the distribution of mercury in the organs have substantially differed between low and high doses. There was a significant tendency to high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The results of this study showed that the accumulation of mercury in kidney and liver tissue increased in groups receiving mercury. The concentration of mercury in the blood was variable and unreliable [ 2 ]. This could be due to its excellent ability to clear toxins and compounds from the kidney and increase blood flow to the kidney [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the accumulation of mercury in kidney and liver tissue increased in groups receiving mercury. The concentration of mercury in the blood was variable and unreliable [ 2 ]. This could be due to its excellent ability to clear toxins and compounds from the kidney and increase blood flow to the kidney [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mercury dissolves in serum, attaches to the membrane of red blood cells, and is transmitted to the brain. Mineral mercury crosses the placenta and the blood-brain barrier and easily accumulates in the fetal brain [ 2 ]. In addition to the brain, mercury can accumulate in the thyroid, myocardium, muscles, adrenal glands, liver, kidneys, sweat glands, pancreas, enterocytes, salivary glands, testes, and prostate whereas impairs the function of these organs [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%